Delirio e gioco d’azzardo: la fuga dalla realtà - Generani, Valentina; Marchesi, Serena (Mission - Open Access, 2024)
This article aims to highlight, through the narration of a clinical case, the possible interactions between Pathological Gambling Disorder and psychotic symptoms; in particular we talk about delirium within a NAS Psychosis, through the narration of a clinical case of a patient who passed through the Lodi Addiction Service.